The Relationship between Level of D-Dimer Serum with Mortality in Acute Stroke Patiens with COVID-19 - Moch Syahrial Pramudia Tarmidi; Mochamad Bahrudin (Department of Neurology Faculty of Medicine Universitas Sebelas Maret, 2024)
Background: COVID-19 has significantly increased morbidity and mortality in Indonesia, particularly at Gambiran General Hospital in Kediri, East Java, following the WHO's pandemic declaration. The global incidence of acute stroke with COVID-19 is 1.4%, presenting varying clinical features from mild to severe outcomes, and even death. The identification of specific biomarkers, such as elevated D-dimer serum levels, is crucial for predicting severe complications in acute stroke patients with COVID-19. Objective: This study aimed to explore the correlation between elevated levels of mild, moderate, and severe D-dimer serum and mortality in acute stroke patients with COVID-19. Methods: Conducted as an observational analytical study using a cross-sectional approach, this research utilized secondary data from medical records at Kediri Gambiran General Hospital (March 2020 to June 2023). Inclusion and exclusion criteria were applied to hospitalized patients, categorized based on D-dimer levels: normal, mild, moderate, and severe. Statistical analyses, including the Spearman correlation test and Chi-square correlation test, were employed to assess the relationship between D-dimer levels and total mortality. Results: Among the 101 enrolled patients, 53 were male (52.48%), with 90 exhibiting elevated D-dimer levels. Out of these, 44 patients died. The Spearman correlation test showed a non-significant value of 0.069 (p>0.005). The Chi-square correlation test for mild, moderate, and severe D-dimer levels on total mortality also yielded a non-significant value of 0.878. Conclusion: This study found no significant relationship between elevated levels of mild, moderate, and severe D-dimer serum and mortality in acute stroke patients with COVID-19 at Gambiran General Hospital.